Answer:
2
Step-by-step explanation:
![(\frac{3}{4})^6 \times (\frac{16}{9})^5=(\frac{4}{3})^{x+2}](https://tex.z-dn.net/?f=%28%5Cfrac%7B3%7D%7B4%7D%29%5E6%20%5Ctimes%20%28%5Cfrac%7B16%7D%7B9%7D%29%5E5%3D%28%5Cfrac%7B4%7D%7B3%7D%29%5E%7Bx%2B2%7D)
![\frac{3^6}{4^6} \cdot \frac{16^5}{9^5}=\frac{4^{x+2}}{3^{x+2}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E6%7D%7B4%5E6%7D%20%5Ccdot%20%5Cfrac%7B16%5E5%7D%7B9%5E5%7D%3D%5Cfrac%7B4%5E%7Bx%2B2%7D%7D%7B3%5E%7Bx%2B2%7D%7D)
![\frac{3^6}{4^6} \cdot \frac{(4^2)^5}{(3^2)^5}=\frac{4^{x+2}}{3^{x+2}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E6%7D%7B4%5E6%7D%20%5Ccdot%20%5Cfrac%7B%284%5E2%29%5E5%7D%7B%283%5E2%29%5E5%7D%3D%5Cfrac%7B4%5E%7Bx%2B2%7D%7D%7B3%5E%7Bx%2B2%7D%7D)
![\frac{3^6}{4^6} \cdot \frac{4^{10}}{3^{10}}=\frac{4^{x+2}}{3^{x+2}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E6%7D%7B4%5E6%7D%20%5Ccdot%20%5Cfrac%7B4%5E%7B10%7D%7D%7B3%5E%7B10%7D%7D%3D%5Cfrac%7B4%5E%7Bx%2B2%7D%7D%7B3%5E%7Bx%2B2%7D%7D)
![\frac{3^6}{3^{10}} \cdot \frac{4^{10}}{4^6}=\frac{4^{x+2}}{3^{x+2}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5E6%7D%7B3%5E%7B10%7D%7D%20%5Ccdot%20%5Cfrac%7B4%5E%7B10%7D%7D%7B4%5E6%7D%3D%5Cfrac%7B4%5E%7Bx%2B2%7D%7D%7B3%5E%7Bx%2B2%7D%7D)
![3^{-4} \cdot 4^{4}=4^{x+2}3^{-(x+2)}](https://tex.z-dn.net/?f=3%5E%7B-4%7D%20%5Ccdot%204%5E%7B4%7D%3D4%5E%7Bx%2B2%7D3%5E%7B-%28x%2B2%29%7D)
This implies
x+2=4
and
-(x+2)=-4.
x+2=4 implies x=2 since subtract 2 on both sides gives us x=2.
Solving -(x+2)=-4 should give us the same value.
Multiply both sides by -1:
x+2=4
It is the same equation as the other.
You will get x=2 either way.
Let's check:
![(\frac{3}{4})^6 \times (\frac{16}{9})^5=(\frac{4}{3})^{2+2}](https://tex.z-dn.net/?f=%28%5Cfrac%7B3%7D%7B4%7D%29%5E6%20%5Ctimes%20%28%5Cfrac%7B16%7D%7B9%7D%29%5E5%3D%28%5Cfrac%7B4%7D%7B3%7D%29%5E%7B2%2B2%7D)
![(\frac{3}{4})^6 \times (\frac{16}{9})^5=(\frac{4}{3})^{4}](https://tex.z-dn.net/?f=%28%5Cfrac%7B3%7D%7B4%7D%29%5E6%20%5Ctimes%20%28%5Cfrac%7B16%7D%7B9%7D%29%5E5%3D%28%5Cfrac%7B4%7D%7B3%7D%29%5E%7B4%7D)
Put both sides into your calculator and see if you get the same thing on both sides:
Left hand side gives 256/81.
Right hand side gives 256/81.
Both side are indeed the same for x=2.
It would be In between 1/2 and 2
Answer:
(0,4) and (-2,0)
Step-by-step explanation:
y=3x²+4x+4
y = -2x +4
3x²+4x+4 = - 2x +4
3x²+6x=0
3x(x+2)=0
x=0, x= -2
x=0, y=-2x+4= -2*0 + 4 =4, (0,4)
x= - 2, y = 2x + 4= 2*(-2) +4=0, (-2,0)
Answer:
52 - 10 = 42
Step-by-step explanation:
Answer:
34 cups
Step-by-step explanation:
just multiply the value in quarts by the conversion factor 4. So, 8.5 quarts times 4 is equal to 34 cups